2021
DOI: 10.1007/s11664-021-09186-y
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Generation Process of a Triangular Single Shockley Stacking Fault Expanding from the Surface Side in 4H-SiC PIN Diodes

Abstract: A triangular single Shockley stacking fault (1SSF) in 4H-SiC, expanding from the surface to the substrate/epilayer interface, was investigated. The triangular 1SSF was observed during electroluminescence examination of PIN diodes that had line-andspace anodes with open windows. The threshold current density of the 1SSF expansion was comparatively intermediate, and differed from that of a 1SSF that expanded from a basal plane dislocation (BPD) that had penetrated from the substrate into the epilayer, and from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The contrast of the defect disappears with the diffraction vector of [0004]. According to the g · b contrast analysis, this type of the horizontal-ridge defect is attributed to Shockley-type SF. ,, High-angle annular dark-field scanning TEM (HAADF-STEM) further verifies that the atomic structure of the horizontal-ridge defect is a SF, with the stacking sequence of (3,3) in Zhdanov’s notation. The stacking sequence of the Si–C bilayers of the horizontal-ridge region is identical to that of 6H-SiC. , …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The contrast of the defect disappears with the diffraction vector of [0004]. According to the g · b contrast analysis, this type of the horizontal-ridge defect is attributed to Shockley-type SF. ,, High-angle annular dark-field scanning TEM (HAADF-STEM) further verifies that the atomic structure of the horizontal-ridge defect is a SF, with the stacking sequence of (3,3) in Zhdanov’s notation. The stacking sequence of the Si–C bilayers of the horizontal-ridge region is identical to that of 6H-SiC. , …”
Section: Resultsmentioning
confidence: 90%
“…Shockley-type SFs can be inherited from the seed crystal or originate from the dissociation of basal plane dislocations. , The Frank-type SFs are created by climbing of an out-of-plane displacement, which inserts or removes a Si–C bilayer in 4H-SiC. Frank-type SFs are mostly formed by the 2D nucleation or by the conversion from threading screw dislocations (TSDs) during the single-crystal growth. , Various characterization methods, such as X-ray topography (XRT), photoluminescence (PL), cathodoluminescence (CL), and electroluminescence (EL), have been used to investigate the properties of SFs in 4H-SiC single crystals. Transmission electron microscopy (TEM) observations have revealed that the stacking sequences of Si–C bilayers of Shockley-type SFs include (3, 1), (6, 2), (5, 3), and (4, 4) in Zhdanov’s notation, and Frank-type SFs have the stacking sequences of (4, 1), (4, 2), and (5, 2). The local PL, CL, and EL investigations indicate that the luminescence peaks of SFs in 4H-SiC locate in the range from 420 to 500 nm. ,, The transition between a threading edge dislocation (TED) and a Shockley-type SF as well as the transition between a TSD and a Frank-type SF are also found in XRT, TEM, and EL observations. , However, these technologies mainly concentrate on the nanoscale atomic structures as well as local electronic and optical properties of a SF in 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by synchrotron X-ray-topography (XRT) and transmission-electron-microscopy (TEM) investigations, TMDs dominate the configurations of the TSD/TMDs in 4H-SiC, while the effect of TMDs on the leakage current of 4H-SiC based high-power devices is still ambiguous (Onda et al, 2013;Konishi et al, 2019;Shinagawa et al, 2020). Meanwhile, the leakage current originating from BPDs was found in 4H-SiC p-n diodes and bipolar junction transistors (BJTs) (Muzykov et al, 2009;Skowronski and Ha, 2006;Ota et al, 2021). Because of the different Burgers vectors, different types of dislocations would generate different atomic disorders in 4H-SiC, and thus different degrees of the leakage current in 4H-SiC based high-power devices (Berechman et al, 2010;Nishio et al, 2022;Senzaki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…42) Electroluminescence (EL) and PL imaging experiments suggest that this type of 1SSF terminates near the substrate/epilayer interface. 44) However, the detailed structure in the deepest part of the epilayer remained unclear. Previous physical analysis has found that the originating BPD was too short to be identified by PL imaging or X-ray topography, and must therefore have been a small segment.…”
Section: Introductionmentioning
confidence: 99%